2015
DOI: 10.1111/ijfs.12952
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant activities of Thai pigmented rice cultivars and application in sunflower oil

Abstract: Summary An analytical comparison for active chemical compounds and their antioxidant activities between three representative pigmented Thai rice cultivars was performed. It was revealed that the darkest purple‐red cultivar (Kum Doi Musur, KDM) contained the highest total phenolic content of 1164.6 mg gallic acid equivalent per100 g (dry basis, db) and the highest total monomeric anthocyanin content of 381.7 mg per100 g (db), when compared with the purple cultivar (Riceberry) and the red cultivar (Sungyod). Its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 30 publications
(52 reference statements)
3
7
1
Order By: Relevance
“…Table 2 shows that TAC in RB was higher in non-polished samples and the effect was more pronounce in parboiling treatment. This result confirms that rice bran is the source of anthocyanin in RB as has been reported previously [37]. Similarly, the highest TPC content was also observed in RB.…”
Section: Effect On Glycemic Index (Gi) and In Vitro Starch Digestibilitysupporting
confidence: 91%
“…Table 2 shows that TAC in RB was higher in non-polished samples and the effect was more pronounce in parboiling treatment. This result confirms that rice bran is the source of anthocyanin in RB as has been reported previously [37]. Similarly, the highest TPC content was also observed in RB.…”
Section: Effect On Glycemic Index (Gi) and In Vitro Starch Digestibilitysupporting
confidence: 91%
“…Anggraini et al (2015) showed that the rice colour presented a correlation with the antioxidant activity for red and purple rice, the darker the colour of rice, the higher the antioxidant activity. These results are in well harmony with those reported for Thai pigmented rice cultivars (Daiponmak et al, 2014;Chinprahast et al, 2016). Mir et al (2016) and Liu et al (2015) demonstrated that brown rice contains a significant amount of antioxidants by the determination of the total polyphenol content, the total flavonoid content and the antioxidant activity of different varieties of brown rice.…”
Section: Rice Matrixsupporting
confidence: 88%
“…The colour of the pericarp is mainly related to the type and concentration of the polyphenols in the rice grain (Kim et al, 2014a). These results are in well harmony with those reported for Thai pigmented rice cultivars (Daiponmak et al, 2014;Chinprahast et al, 2016). In the last years, some studies have been published that assess the polyphenols content and antioxidant capacity of rice as function of the different rice colour variety (Table 1).…”
Section: Rice Matrixsupporting
confidence: 80%
“…Also, some plants extract containing flavonoids or polyphenols have been applied to edible oil, negatively affecting oxidation (Sekhon‐Loodu et al., 2013; Ye et al., 2015). However, the antioxidant effect of anthocyanins in oil system is relatively poor, compared with flavonoids or polyphenols (Chinprahast, Tungsomboon, & Nagao, 2016; Shantha & Decker 1994). Likewise, the crude extract of dark purple–red rice cultivar showed some ability to prevent lipid peroxidation, whereas its activity is inferior to that of BHA; BHT outperforms BHA in inhibiting biodiesel oxidation (Domingos et al., 2007).…”
Section: Resultsmentioning
confidence: 99%